2002
DOI: 10.1007/s00464-001-8239-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medicine: open and laparoscopic bariatric surgery

Abstract: Randomized controlled trials comparing the various laparoscopic operations are strongly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 119 publications
1
30
0
7
Order By: Relevance
“…Moreover, we found that IT was associated with a shorter duration of surgery (50.82 [SD 8.49 [SD 14.7] h; p < 0.001) and a significant decrease in both major and minor postoperative complications compared with BPD. In contrast, bypass procedure research in humans showed that the overall early complication rate ranges from 3% to 15%, 41,42 and because of possible iron and vitamin B 12 deficiency, there is a need for long-term supervision and vitamin and mineral replacement. 43 Both operations appear to be reasonably safe, with low 30-day mortality, particularly considering that this series includes our initial experience with IT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that IT was associated with a shorter duration of surgery (50.82 [SD 8.49 [SD 14.7] h; p < 0.001) and a significant decrease in both major and minor postoperative complications compared with BPD. In contrast, bypass procedure research in humans showed that the overall early complication rate ranges from 3% to 15%, 41,42 and because of possible iron and vitamin B 12 deficiency, there is a need for long-term supervision and vitamin and mineral replacement. 43 Both operations appear to be reasonably safe, with low 30-day mortality, particularly considering that this series includes our initial experience with IT.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, laparoscopic surgery has gained wide acceptance and is now more common in primary procedures in bariatric surgery than the open approach. [14][15][16] Regardless of the method used to perform any particular weight loss procedure the surgical endpoints are the same. All primary bariatric procedures can generally be performed laparoscopically with clinical results comparable to those of an open counterpart.…”
Section: Laparoscopic Vs Open Approachmentioning
confidence: 99%
“…6. Todos los autores destacaron (también corroborado por nosotros), que la vía laparoscópica es difícil y requiere de una curva de aprendizaje que va entre 75 y 100 cirugías 5,6,9 . Se ha considerado una de las cirugías más complejas del tracto gastrointestinal, por lo que los cirujanos que se dedican a obesidad mórbida debieran tener una amplia experiencia previa, tanto de cirugía gastrointestinal abierta, como en cirugía laparoscópica.…”
Section: Comentario Generalunclassified
“…Esto significa entregar la mejor experiencia clíni-ca con la mejor evidencia disponible de la literatura quirúrgica internacional 6 . Por lo tanto, en este artículo se revisará la mejor evidencia disponible que permita aclarar si el más recomendable abordaje para realizar un bypass gás-trico es la vía laparotómica o la vía laparoscópica, de acuerdo a 2 parámetros: a. Meta-análisis y revisiones de gran número de pacientes operados.…”
unclassified